Sialidosis type I: ophthalmological findings. (16th October 2014) - Sobral, Isa; Cachulo, Maria da Luz; Figueira, João; Silva, Rufino
Abstract : Sialidosis is a lysosomal storage disease caused by deficit of neuraminidase. It is an autosomal recessive disease, heterogeneous in its onset, presentation and prognosis. We report a case of a male patient with molecular and enzymatic confirmation of the diagnosis. Symptoms began at age 26 with reduced visual acuity, bilateral cherry-red spots and later myoclonus. A brother, now deceased, had the same confirmed disease. We describe the symptoms and clinical findings of the patient, as well review the current knowledge on the topic. With this report, we highlight the importance of a clinical history integrating all the patient's symptoms in order to achieve the diagnosis. In the presence of a cherry-red spot, a comprehensive study is mandatory. Despite being a rare disease, sialidosis carries a significant burden for its patients and its diagnosis should always be considered in the appropriate setting.